Career aspiration and related contextual variables - Muna Abdullah Al-Bahrani; Suad Mohammed Allawati; Yousef Abdelqader Abu Shindi; Bakkar Suliman Bakkar (International Journal of Adolescence and Youth, 2020)
This study examines the differences between male and female adolescents and their maths study on their career aspiration. The study investigates the effect of grade point average and parents’ educational level on adolescents reported career aspiration. A career aspiration scale is administered to 2717 students representing tenth and eleventh grades. The findings reveal females have higher scores on career aspiration than males. Students who study pure maths in their career path have higher score on career aspiration than those with applied maths. Results also show significant effects of parents’ educational level and grade point average on adolescents’ career aspiration. Suggestion is provided to consider contextual variables in designing interventions.